Crime prevention in Islamic financial institutions: practices in Brunei Darussalam / Noraini Mohamad, Mohamad Asri Abdullah and Nawal Kassim - Mohamad, Noraini; Abdullah, Mohamad Asri; Kassim, Nawal (Universiti Teknologi MARA Cawangan Selangor, 2010)
The Islamic Financial Institutions (IFIs) in Brunei Darussalam have experienced a significant growth and become new players in the banking industry. The State continues to offer new Islamic innovative banking products and services in order to gain acceptance from the public and increase market shares of the industry. Strategically, the State aims to be the global player in Islamic banking activities and this is evidenced through the mergers of their two large Islamic Financial Institutions namely, the Islamic Brunei Bank Berhad (IBB) and Islamic Development Bank Berhad (IDB) to form Bank Islam Brunei Darussalam (BIBD). Though the merger has successfully increased BIBD’s total assets, branches and ATMs, BIBD in particular or the Ministry of Finance in general lacks the Islamic Financial Criminology (IFC) guidelines for Islamic Financial Crime prevention on Islamic products and services offered by IFIs in the State. Similarly, in Brunei and Malaysia the power to prevent Islamic financial criminology practices is vested within the Civil Court and not within the Syari’ah jurisdiction. Conflicts arise when the judgment of Civil Court on matters pertaining to Islamic financial criminology are based on conventional practices. Thus, this paper aims to examine the background of Islamic financial criminology crime prevention in the banking system in Brunei Darussalam and suggests improvement to support the development of an Islamic financial system in the State.